PROPORTIONAL VS MAJORITARIAN DEPUTIES: COMPARATIVE ANALYSIS OF ACTIVITIES IN KHARKIV REGION - Зінченко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The activity of the Ukrainian members of parliament (MPs) of eighth convocation, which were elected in the Kharkiv oblast, is analyzed. A comparison of the activities between deputies elected under a majoritarian system and the ones from the lists of political parties is made. MPs` activity was analyzed in terms of plenary and committee attendance, participation in voting, legislative activity, submission of deputy inquiries and speeches at plenary meetings. The Kharkiv region in the Verkhovna Rada of Ukraine is represented by 23 deputies who represent the fractions: the Petro Poroshenko Bloc Party, the Narodniy Front political party, the Opposition Bloc political party, the Samopomich political party, Oleg Lyashko’s Radical Party, the group «Volya Narodu», the «Vidrodzennya» group, that is, almost all fractions and groups, that is a high indicator in comparison with other regions. The paper shows that despite the great representation, the efficiency is low and ineffective. Deputies missed a large number of plenary sessions without respected reason – 3 MPs attended less than 30% of plenary sessions. MPs are very passive in their duty to take part in polls during plenary sessions - 12 out of 23 deputies, that is, more than half, have a voting participation rate less than 17%. The activity of deputies is characterized as «legislative spam» - the average percentage of the adopted bills in the number of submitted ones is under 10%. Most representatives of the Kharkiv region almost do not use their right to make a deputy request and to speak in the plenary hall –7 deputies submitted less than five deputy inquiries, 6 deputies never spoke during plenary sessions. It was noted that deputies elected by either of the two electoral systems may demonstrate high and low rates. The most productive deputies of the Kharkiv region by the selected indicators are majoritarian Alexander Kirsch (Narodniy Front ) and Roman Semenukha selected from the Samopomich  party list, the least productive ones are majoritarian Dmitry Dobkin (self-nominee) and Mikhail Dobkin selected from the Opposition Bloc party list.